2015
DOI: 10.3928/01484834-20150417-03
|View full text |Cite
|
Sign up to set email alerts
|

Underrepresented Students’ Perspectives on Institutional Climate During the Application and Admission Process to Nursing School

Abstract: Findings provide direction for developing programming and collaborations to enhance the institutional climate for underrepresented nursing applicants. [J Nurs Educ. 2015;54(5):261-269.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Previous studies have identified that men are underrepresented in nursing course applications; however BSA men do not seem to align with this trend according to this review [24]. They are increasing in numbers of applications and are more likely to apply than their British White male counterparts.…”
Section: Application Ratesmentioning
confidence: 58%
See 1 more Smart Citation
“…Previous studies have identified that men are underrepresented in nursing course applications; however BSA men do not seem to align with this trend according to this review [24]. They are increasing in numbers of applications and are more likely to apply than their British White male counterparts.…”
Section: Application Ratesmentioning
confidence: 58%
“…Whist there has been a longstanding recognition of the lack of nurses in the NHS; the existing evidence base suggests that a particular range of barriers exist for BAME people and men when trying to enter the nursing workforce [22][23][24][25][26][27][28][29]. These barriers include, lack of knowledge of nursing course requirements, poor experiences of nursing education, as well as lack of male nurse role models [2,[30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…The methodology used to collect data, and how that data is utilized by the admission committee (eg, weighing lived experiences, vs. relying solely on standardized test scores) also have a direct impact on selection. [18][19][20][21] The Pharmacy College Application Service (PharmCAS), the centralized application service for pharmacy schools, is used by the majority of pharmacy schools (126 of 139). Given the large percentage of participation by colleges and schools of pharmacy, the data collected by PharmCAS plays a significant role in the selection process of future student pharmacists.…”
Section: Recruitment and Student Admissionsmentioning
confidence: 99%
“…The responsibility in ensuring a diverse nurse population begins with the undergraduate nursing education and faculty. Historically, nursing has actively sought males and other diverse groups by utilizing recruiting strategies and marketing ploys (Fillman, 2015; Woods-Giscombe et al, 2015). It must be noted that there has been some progress made in the recruitment of some ethnic groups such as Latinos and Blacks (American Association of Colleges of Nursing [AACN], 2016).…”
Section: Introductionmentioning
confidence: 99%